The Christian Evangelism Work With the Seemingly Non-Traditional Wear in Ghana (Global Journal of Human-Social Science, 2022)
To many religious organizations clothing is an important identifiable mark Within the Christian religion for example each of the various subgroups within one denomination women s fellowship choir brigade singing band evangelism group has a unique clothing worn on meeting days to set it apart from other groups and this is in conformity with one of the popular definitions of clothing which says in part that clothing is anything that is put on the body either permanently or temporally that makes us look different Clothing throughout history has been developed for protection modesty and decoration and functions as a tool for communication that gives several meanings to our appearance the kind of person self we are our mood and values which together may express appreciation or displeasure A dress as we all know that is incorrectly worn or is inappropriate to a place or situation may bring a feeling of discomfort to the wearer and raise eye brows or provoke looks of anger from others This study focuses on the impact of traditional wears on the religious activities of the men in two Christian denominations which have as their hallmark the zeal for the evangelism characterized by visiting people in their homes and conducting one on one bible studies with them
Keywords: evangelism; traditional wears